2018
DOI: 10.1007/s00442-018-4078-6
|View full text |Cite
|
Sign up to set email alerts
|

A natural history model of New England salt marsh die-off

Abstract: Natural history gave birth to ecology and evolutionary biology, but today its importance is sometimes marginalized. Natural history provides context for ecological research, a concept that we illustrate using a consumer-driven vegetation die-off case study. For three decades, local predator depletion promoted the formation of high-density crab (Sesarma reticulatum) grazing and burrowing fronts, resulting in the spread of vegetation die-off through southern New England and Long Island marshes. We review results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Complementing this perspective, there has been an emerging focus on biological factors, especially consumers, such as mammals (Bakker et al 1993), birds (Jefferies et al 2006), and snails (Silliman et al 2005). Conceptually, to advance estuarine theory, as well as for applied management, there is a need to better understand the relative importance of different drivers of marsh sustainability, and how they vary across scales (Pettengill et al 2018). The scale of most crab studies is typically small (plots within a marsh), while the scale of studies assessing sea-level rise is typically larger (entire estuary or region).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementing this perspective, there has been an emerging focus on biological factors, especially consumers, such as mammals (Bakker et al 1993), birds (Jefferies et al 2006), and snails (Silliman et al 2005). Conceptually, to advance estuarine theory, as well as for applied management, there is a need to better understand the relative importance of different drivers of marsh sustainability, and how they vary across scales (Pettengill et al 2018). The scale of most crab studies is typically small (plots within a marsh), while the scale of studies assessing sea-level rise is typically larger (entire estuary or region).…”
Section: Introductionmentioning
confidence: 99%
“…The scale of most crab studies is typically small (plots within a marsh), while the scale of studies assessing sea-level rise is typically larger (entire estuary or region). Conceptually, to advance estuarine theory, as well as for applied management, there is a need to better understand the relative importance of different drivers of marsh sustainability, and how they vary across scales (Pettengill et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of vegetation properties on spatial patterns in this valuable ecosystem is still poorly understood. Previous studies mainly focused on the effects of vegetation zonation on spatial patterns [2,[26][27][28][29][30]. These vegetation zonation studies reported various influential factors; highly influential factors are: Inundation time [2,26,31,32], wave forcing [33][34][35][36][37], competition [2,38,39], and creek influence [26,27,31,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…On adjacent, higher-elevation marsh platforms, dense root mats cause the substrate to be too hard for Sesarma burrowing (>2 kg⋅cm −2 ; refs. 29 and 37 ). Recent research has suggested that if sea-level rise outpaces salt-marsh vertical accretion, the resulting extension in the duration of tidal flooding will drive a shift in plant-tissue allocation from dense-packed fine roots to larger rhizomes that better aerate the soil and increase pore space, thereby softening the marsh platform and enhancing the system's overall vulnerability to Sesarma intensive burrowing and overgrazing ( 29 ).…”
mentioning
confidence: 98%
“…Since the 1970s, high-density Sesarma fronts that leave denuded, burrow-riddled creekbanks in their wake ( 34 ) have been documented from New York to Massachusetts ( 35 ), particularly where recreational fishing has extirpated Sesarma ’s predators ( 36 ). In the northeastern United States, Sesarma fronts form exclusively on lower-elevation creekbanks, where elevated water velocities flush sediment and toxins from their burrows, Sesarma recruitment rates are high, and marsh substrates exhibit suitable hardness (∼1.4 kg⋅cm −2 ) for Sesarma burrow excavation and maintenance ( 37 ). On adjacent, higher-elevation marsh platforms, dense root mats cause the substrate to be too hard for Sesarma burrowing (>2 kg⋅cm −2 ; refs.…”
mentioning
confidence: 99%